Mobile Cipta Puisi: An Innovative Application for Learning Poetry Writing - Kartini, Ari; Sunendar, Dadang; Sumiyadi, Sumiyadi; Yulianeta, Yulianeta; Nurjamin, Asep; Maulana, Cepri (International Journal of Language Education, 2025)
This study aims to describe the utilization of innovative media in learning to write poetry developed in the form of a mobile application. This research uses the Research and Development (R&D) method by adopting the R2D2 model, which focuses on three main stages: (a) determination, (b) design and development, and (c) dissemination. The research approach used was descriptive quantitative, with data obtained through the assessment of media experts, material experts, and 105 student users of the application using a Likert scale questionnaire. Data analysis was carried out using the Gregory matrix technique and the calculation of the response scale. The results of this study show that: (1) Validation by media experts and material experts with the Gregory matrix resulted in a score of 1.0, which was interpreted as ‘very high’ validity; (2) User assessment of the MCP application obtained a score of 3.575, which fell into the ‘Very Good’ category; (3) Input from experts and users generally includes aspects of completeness of instructions for use, visual appearance, material enrichment, and provision of poetry anthologies from contemporary poets. The success of this application is due to the application of good instructional design and usability principles so that appearance and navigation are considered optimal. In addition, the utilization of technology that meets user needs also supports the high validity of the media. Meanwhile, the material is highly valid based on theoretical studies, fulfillment of user needs, and expert involvement in the development process. Thus, this research significantly contributes to improving the effectiveness of poetry learning while encouraging innovation in the development of digital learning media.